If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 + -3x = 11 + -12x + -13 Reorder the terms: 9 + 7x + -3x = 11 + -12x + -13 Combine like terms: 7x + -3x = 4x 9 + 4x = 11 + -12x + -13 Reorder the terms: 9 + 4x = 11 + -13 + -12x Combine like terms: 11 + -13 = -2 9 + 4x = -2 + -12x Solving 9 + 4x = -2 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 9 + 4x + 12x = -2 + -12x + 12x Combine like terms: 4x + 12x = 16x 9 + 16x = -2 + -12x + 12x Combine like terms: -12x + 12x = 0 9 + 16x = -2 + 0 9 + 16x = -2 Add '-9' to each side of the equation. 9 + -9 + 16x = -2 + -9 Combine like terms: 9 + -9 = 0 0 + 16x = -2 + -9 16x = -2 + -9 Combine like terms: -2 + -9 = -11 16x = -11 Divide each side by '16'. x = -0.6875 Simplifying x = -0.6875
| y=-11(-1)+6 | | 0=x^3+12000*x+10 | | x+54=81 | | -3(y-2y)+9=-6(2y-y)+6+8y | | x-3.92=4.74 | | 10=1/5 | | z=8-8i | | 6x-1=4x+29 | | 6-3x=-6x+15 | | x-28=25 | | 7x+6-9x=15-15x+13x-9 | | 7x+5=-15+5 | | 4(3-x)-2(3x-4)=-(16-x) | | 8y=6(y+2.50) | | 7x+5=-15+3x | | 6(3+3x)-4=122 | | 2x-12=o | | 5/4=1-1/4 | | 75=15(2x+1) | | x^3+2x^2-20x+24=0 | | 2(3x+4)+5(3x-5)=3(x-7)+8 | | 3x+2=2x+x-1 | | 7x(2x+3)=56 | | p^2+x^2y^2q^2=x^2z^2 | | 5=6p | | 6+2x-1=9x+7-6x | | 3d+5+17= | | x(y+2)+y=1 | | 2(3x-1)=3x-2 | | x-x*0.1=500 | | 9y-9y^2-2=0 | | t-1.5=5 |